Cytotoxicity and anti-inflammatory activities of garcinia xanthochymus extracts on cell lines - Hamidon, Hanisuhana; Bakhtiar, M. Taher (2014)
Natural products have been recognized and utilized by humans in management of disease, injuries and other health problems. This study was conducted to evaluate cytotoxic and anti- inflammatory activities of Garcinia xanthochymus extracts on cell lines. Roots and stem barks of plant were extracted using maceration method with n-hexane, dichloromethane and methanol successively. Cytotoxic activity of the extracts was tested against MCF-7 breast adenocarcinoma using MTT assay. Anti-inflammatory study was evaluated using RAW 264.7 mouse macrophage cells. Cell viability study of extracts against cell line was first done using MTT assay. Then, chosen safe concentration was used in the nitric oxide production study in LPS-stimulated cells that based on Griess reagent reaction. The result of cytotoxicity study showed that dichloromethane and n-hexane extracts of root and stem bark exhibited cytotoxic activity in dose-dependent manner. Meanwhile, for anti-inflammatory study, all root extracts together with stem bark dichloromethane and n-hexane extracts reduce NO production in LPS-stimulated cells in dose dependent manner. As conclusion, these finding indicated that G. xanthochymus extracts may become interesting candidate for treatment of cancer and inflammation.